`2y + x = 4x=2y`

To start, express the given as two equations.

EQ1: `2y+x = 4x`

EQ2: `2y = 4x`

Then, let's try to express EQ1 as one variable. To do so, substitute EQ2 to EQ1. So, replace the 2x in EQ1 with 4x.

`2y+x = 4x`

Since all the terms have the x variable, bring them together on one side of the equation.

`4x+x-4x =0`

`x=0`

Then, substitute value of x to either EQ1 or EQ2 and solve for x.

`x = 0` , `2y=4x` `2y=0`

`2y=4*0` `y=0`

**Hence, the solution to the given equation is `x=0` and `y=0` .**

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now